The Role of Digital and Virtual Teams in Project Management: Zambia Centre for Communications (International Journal of Scientific Research and Management (IJSRM), 2022)
The study was designed to explore the role of digital and virtual teams in project management. The study addressed three specific objectives and these were: To identify the benefits of digital and virtual teams in project management; to compare and contrast the elements and components of virtual project management and the traditional project management and to establish challenges of the digital and virtual teams in project management. Within a standard quantitative research methodology, the study used an embedded mixed methods design, which entailed the collection and analysis of both quantitative and qualitative data. Questionnaires and interviews were utilized to obtain quantitative and qualitative data from 80 individuals who were chosen for their purpose and convenience. The study established the following as benefits for teams working in remote: Less efforts required, flexible scheduling, lack of commute, cost saving, reduced anxiety/stress, freedom of travel/relocate, reduced office politics and able to live where ever one wanted. With regard to the second objective, the study established that in both modes of project management, there was diversity in national background and culture. There was also communication, setting of goals to be achieved and evaluation of the project outcomes in both modes. Virtual teams, on the other hand, were very different from regular teams. Members of traditional teams worked close to one another, but members of virtual teams worked in various locations. A virtual team also functioned beyond place, time, and organizational boundaries, with linkages strengthened by webs of communication technology, unlike a typical team. On the third objective, the study etablished that virtual project management challenges were categorised into seven classes thus: communication; isolation and confusion; developing trust; performance, diversity and virtual work-cycle management; free ride; cultural differences; and time zones. Based on the findings, the study recommends that to avoid the aspect of employee isolation, project managers must frequently use audio-video calls during virtual meetings. Second, virtual managers and their employers should build on the perceived benefits found in this study both before and throughout the development and management of virtual project teams.